Other people's children - Trollope, Joanna (London : Black Swan, 1999)
When a man and a woman get married, things can get complicated. When they have children from previous marriages, "complicated" can become the understatement of the year. From the grown daughter who insinuates herself into her widowed father's romantic life, to the sullen teenager whose loyalties lie with her estranged mother; from the awkwardness of tense celebrations to the discovery of surprising sources of strength, Joanna Trollope reveals the laughter and tears, the tension and the tenderness, that live behind the statistics and stereotypes about stepfamilies.
Originally published: London: Bloomsbury, 1998.
76617
Keywords: Stepfamilies -- Fiction. -- England; Parent and child -- Fiction. -- England; Children of divorced parents -- Fiction. -- England